Tick-Borne Pathogens in Dermacentor reticulatus Ticks from Bosnia and Herzegovina - Teufik Goletić; Darinka Klarić Soldo; Naida Kapo; Šejla Goletić; Amira Koro-Spahić; Amra Alispahić; Adis Softić; Vedad Škapur; Jasmin Omeragić (Pathogens, 2024)
Dermacentor (D.) reticulatus ticks carry and transmit a wide range of pathogens to vertebrate hosts. Limited information is available about the existence of emerging tick-borne pathogens and the distribution of D. reticulatus in Bosnia and Herzegovina. The study aimed to investigate the occurrence and distribution of D. reticulatus and to detect the presence of Anaplasma spp., Borrelia (B.) burgdorferi s.l., Rickettsia spp., and Babesia spp. in samples originating from questing ticks and ticks collected from domestic animals in various regions of Bosnia and Herzegovina. A total of 402 collected D. reticulatus ticks were widely distributed throughout the country. Of the 41 pools consisting of 205 individual D. reticulatus ticks, 21 (51.2%) indicated the presence of Rickettsia spp., 17 (41.4%) of Babesia spp., 2 (4.8%) of Anaplasma spp., and 1 (2.4%) of B. burgdorferi s.l. after real-time PCR screening. Our study indicates that D. reticulatus has significantly expanded its distribution and host range in Bosnia and Herzegovina. Moreover, our results represent the first detection of Babesia spp. in D. reticulatus in Bosnia and Herzegovina. Given the demonstrated presence of emerging pathogens in questing and feeding ticks, there is an urge to establish a surveillance system for ticks and tick-borne pathogens in Bosnia and Herzegovina.